with the assistance of Kīn Mātsūmūtū, Hīrūmūtǧī ’Ūkūǧī, Hīrūtūšī Nūmūtū, Kāẓmī Yākī, Kātsūhīkū ’Ūnumā, taqrīr mūǧaz ’an tanqībāt al-bi’ṯah al-yābāniyyah al-’āmilah fī mawqi’ Ǧīkān: al-mawsim al-tānī mašrū’ ’inqād ’āṯār sadd Ṣaḍḍām - Fūǧī, Hidiyū
Fujii Hideo with the assistance of Matsumoto Ken, Oguchi Hiromochi, Numoto Hirotoshi, Yagi Kazumi, Onuma Katsuhiko, Short Report on the Excavations of the Japanese Expedition Working at the Site of Jikan: Second Season, Rescue Project at Saddam Dam: Sumer 43 (1984, ersch. 1987) 281-282 (in Arabic, translated by Ḥikmat Bašīr al-’Aswad).